2017
DOI: 10.1007/s11604-017-0679-y
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of miR-155/FOXO3a and miR-222/PTEN in acquired radioresistance of colorectal cancer cell line

Abstract: These observations indicate that miR-222 and miR-155 could induce radiation resistance in colorectal cancer by targeting PTEN and FOXO3a genes, respectively. Therefore, miR-222 and miR-155 can be suggested as good biomarkers of CRC radiation response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 59 publications
0
28
0
Order By: Relevance
“…It is known that the radioresistance of CRC cells leads to the failure of radiotherapy and toxic impacts of ionizing radiation [20]. Recent evidence has already demonstrated that miRNAs played an important role in radio-induced apoptosis and the radioresistance of CRC cells [21].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the radioresistance of CRC cells leads to the failure of radiotherapy and toxic impacts of ionizing radiation [20]. Recent evidence has already demonstrated that miRNAs played an important role in radio-induced apoptosis and the radioresistance of CRC cells [21].…”
Section: Discussionmentioning
confidence: 99%
“…49 Impairing both miR-155 and miR-200c activities favored epithelium-to-mesenchyme transition and decreased the sensibility to gefitinib of these cell lines in particular by inducing epigenetic modifications. 49 MiR-155 was further shown to induce radioresistance of colorectal cancer cells, by targeting FOXO3a transcripts, 50 and in nasopharyngeal carcinoma tissues, by targeting Ubiquilin 1 transcripts and increasing PI3K and phospho-AKT activity. 51 High levels of miR-155 in contrast enhanced the sensitivity of triple-negative breast cancer cells to irradiation.…”
Section: Dual Roles Of Mir-155 In Cancermentioning
confidence: 99%
“…MiR‐155 was further shown to induce radioresistance of colorectal cancer cells, by targeting FOXO3a transcripts, and in nasopharyngeal carcinoma tissues, by targeting Ubiquilin 1 transcripts and increasing PI3K and phospho‐AKT activity . High levels of miR‐155 in contrast enhanced the sensitivity of triple‐negative breast cancer cells to irradiation.…”
Section: Dual Roles Of Mir‐155 In Cancermentioning
confidence: 99%
“…Notably, miR-155 was widely studied as an oncogene involved in multiple cancers [8][9][10][11][12]. Recently, several studies showed that aberrant expression of miR-155 was tied to the diagnosis and prognosis of lung cancer.…”
Section: Introductionmentioning
confidence: 99%